Finding Balanchine's Lost Ballets : Exploring the Early Choreography of a Master - Kattner, Elizabeth (Book collections on Project MUSE., 2020)
"In the first book to focus exclusively on George Balanchine's early Russian ballets, most of which have been lost to history, Elizabeth Kattner offers new insights into the artistic evolution of a legend through her reconstruction of his first group ballet, Funeral March"--